EFFECT OF FINANCIAL LITERACY, EDUCATION LEVEL AND GENDER ON THE GROWTH OF SMES: EMPIRICAL STUDY ON THE COVID19 PANDEMIC CONDITIONS - Sri Wahyulina; Embun Suryani; Akhmad Saufi; Handry Sudiartha Athar (Master of Management, Mataram University, 2023)
This study aims to examine the effect of Financial Literacy, Education Level and Gender on the Growth of Small and Medium Enterprises (SMEs) in the Creative Economy Sector in the Mandalika Special Economic Zone (SEZ). The data was collected using the survey sample method, and the number of samples in this study was 50 SMEs. The sample was taken using a simple random sampling technique. The independent free variables are Financial Literacy, Education Level and Gender, while the dependent variable is SME Growth. Technique Analysis data is multiple linear regression, which conducted using the 2016 version of SPSS. The results showed that financial literacy and education level have a positive and significant effect on SMEs growth. Meanwhile, gender has a positive, but not significant effect on the growth of SMEs. Keywords: Financial Literacy, Education Level, Gender and SMEs Growth